1986
DOI: 10.1111/j.1600-0536.1986.tb05275.x
|View full text |Cite
|
Sign up to set email alerts
|

Hand eczema in hairdressers and nurses: a prospective study I.

Abstract: A prospective study of the development of hand eczema was initiated in 86 junior hairdressers and 217 junior nurses. Data obtained at the start of their apprenticeships are presented. None of the junior apprentices presented with hand eczema, but a history of hand eczema was reported by 22/303 (7%) of the students. Almost half of this group (10/22, 45%) could be classified as atopics. Students without a history of hand eczema showed a similar frequency of atopy (17%) as observed in the general population. Hist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…The role of nickel as an occupational allergen in hairdressing is a controversial area in contact dermatitis. It has been reported that up to 27% of hairdressers have evidence of nickel sensitivity before significant exposure in the trade (11, 39), which has been attributed to ear piercing and nickel‐plated costume jewellery. No correlation has been found between nickel sensitivity at the onset of apprenticeship and the development of hand eczema after 8 years of follow‐up (4).…”
Section: Discussionmentioning
confidence: 99%
“…The role of nickel as an occupational allergen in hairdressing is a controversial area in contact dermatitis. It has been reported that up to 27% of hairdressers have evidence of nickel sensitivity before significant exposure in the trade (11, 39), which has been attributed to ear piercing and nickel‐plated costume jewellery. No correlation has been found between nickel sensitivity at the onset of apprenticeship and the development of hand eczema after 8 years of follow‐up (4).…”
Section: Discussionmentioning
confidence: 99%
“…There are many causes of occupational skin disease in healthcare workers, the prevalence having been suggested to be about 30% (36). 90% of such dermatoses are localized on the hands and one may assume that various factors favor the development of hand dermatitis (37). The evolution of occupational contact dermatitis is determined by a combination of endogenous and exogenous factors.…”
Section: Discussionmentioning
confidence: 99%
“…There was also a study where patch testing was performed on Dutch HAs who had just enrolled in hairdressing school, which showed that very few students had positive reactions to most contact allergens (1.1% positive for fragrance mixture, 1.1% on PPD and 2.3% on thioglycolic acid) with the exception of nickel (25.6% positive) 34 . From the above‐stated, it can be concluded that a large number of Dutch HAs had already been sensitized to nickel earlier, which seems not to be the case with our apprentices (only one apprentice with a positive patch reaction to nickel—1.6%).…”
Section: Discussionmentioning
confidence: 99%